Does ESG Performance Have An Influence on Enterprise Value? Evidence from Indonesia - Daulay, Anggi Anugerah; Wahyudi, Eri (Universitas Pamulang, 2026)
This study investigates the impact of environmental, social, and governance (ESG) performance on enterprise value in publicly listed companies in Indonesia. Using 69 firm-year observations with complete ESG scores from the Bloomberg Terminal from 2021 to 2023, panel data regression is employed for analysis, which incorporates Tobin's Q as the dependent variable, ESG scores as independent variables, and leverage, firm size, and return on equity as control variables. The results reveal that none of the ESG pillars environmental, social, or governance significantly affect enterprise value suggesting that ESG initiatives do not generate measurable financial benefits in the short run. These findings are consistent with time horizon theory, which suggests that ESG initiatives generate immediate costs while their value creation benefits materialize in the long run. The study presents empirical evidence that in the short-term context, ESG performance is not yet viewed as a value enhancing signal for investors in the Indonesian capital market, highlighting the need for further research over extended observation periods to capture long term sustainability impacts.